Staying Angry: Black Women's Resistance to Racialized Forgiveness in U.S. Police Shootings. Issue 3 (2nd July 2020) - Pearl, Sharrona
Abstract: Requests for forgiveness can effectively silence and delegitimize anger, and requests to publicly perform emotional labor can effectively make that labor both required and undervalued. I focus on interviews and press conferences between 2014 and 2016 with police shooting mourners Esaw Garner, Lesley McSpadden, Samaria Rice, Audrey DuBose, and Valerie Castile. I show how these Black women resist racist calls to deprive them of their anger and right to seek justice, refusing to suture the social crisis of police violence with their emotional labor. On television, the news context obscures the entertainment value of anger and grief that partly motivates these requests. I argue that speakers are well aware of the way supposedly angry, supposedly violent affect gets judged on the Black body in the public sphere. Family members resist the pressure to forgive—a form of resistance that insists on the right to anger in the public sphere—while strategically maintaining a reasonable demeanor.